Formulation of Smart City Policy Instruments (Study Jogja Smart Service Program in Yogyakarta City) - Agustina Rahmawati (Program Pascasarjana Universitas Negeri Makassar, 2020)
This study aims to provide an overview of the formulation of policy instruments in improving public services of the Yogyakarta City. Therefore, this study describes the effectiveness that has been achieved and also describes the problems that arise in the Jogja Smart Service Program (JSS) in the context of the formulation of policy making. This can then be useful for developing alternative policy instruments that are similar. In the perspective of public administration, a program of policy can be seen part of the management of decisions in public policy, where the resources and actors are organized and coordinated. This gives consequences about how the process of making instrument formulation at the time of making the policy. Thus, it becomes interesting to see how the process of formulation of policies in the Jogja Smart Service Program (JSS). By using descriptive qualitative research methods, the stages of the method in this research are collecting data related to the policy formulation process of the Jogja Smart Service Program (JSS), in the form of interviews and documentation of regulations and related policies. The result of the research is the formulation of Jogja Smart Service (JSS) policies in Yogyakarta City which still has various challenges, so a combined instrument is needed, namely synergy and collaboration between the government, private sector, community and other stakeholders to support the effectiveness of the program.